THE IMPACT OF DIGITAL TRANSFORMATION ON INCREASING THE COMPETITIVENESS OF INDUSTRIAL ENTERPRISES (American Journal of Business Management, Economics and Banking, 2025)
The article examines the process of digital transformation and its impact on the competitiveness of industrial enterprises. In modern conditions, digital transformation is perceived as an objective reality reflecting social and economic progress. Its emergence is associated with the fourth industrial revolution, which marked the transition to a post-industrial model of economic development. Special attention is paid to the development of digital technologies capable of changing the structure of economic relations, as well as transforming traditional approaches to production processes, interaction with contractors, logistics, financial operations, personnel management, labor productivity improvement and other business aspects. All this leads to an increased role of artificial intelligence in the activities of enterprises.